Hundred psychiatric outpatients presented with attempted suicide (Health Renaissance, 2011)
Introduction: Suicide is a major public health concern and it is one of the commonest Psychiatric emergencies. Suicide rates are increasing and have become a global concern with more than 600,000 suicidal attempts every year in the United States, alone. There is no national data available for Nepal. This hospital based study may help in understanding about the cause and methods of suicide attempts. Objective: The aim of the present study was to assess the (i) methods and precipitating cause for attempted suicide (ii) to study the relationship between major socio-demographic variables and attempted suicide. This study may be helpful in formulating suicide prevention strategies at different levels. Methods: Cross-sectional study in a tertiary level hospital. Consecutive 100 cases of attempted suicide coming in contact to an investigating team were evaluated for methods opted for attempting suicide and underlying cause was explored. Demographic variables were recorded and analysed. Results: Majority of the suicide attempters (67%) were less than 35 years of age, and female outnumbered male. Sixty one percent of the subject belonged to rural background. Out of 100 suicide attempters 40% of them have completed SLC and majority of them were students. Fifty-four percent of the sample consumed pesticides and 25% of the cases used highly lethal means. Majority of the persons (58%) had psychiatric co morbidities in which depression was the commonest. Interpersonal conflict accounted for 18% of the cases followed by marital problems (13%) as triggering factors of attempted suicide. Conclusion: Majority of the suicide attempters were young and having psychiatric disorders. Most of the attempters were from rural areas. Keywords: Attempted suicide; psychiatric co morbidities; Interpersonal conflict. DOI: http://dx.doi.org/10.3126/hren.v9i3.5584   HR 2011; 9(3): 162-167